2016
DOI: 10.1590/1516-3180.2016.0139140616
|View full text |Cite
|
Sign up to set email alerts
|

A five-year review of vertical HIV transmission in a specialized service: cross-sectional study

Abstract: CONTEXT AND OBJECTIVE: Healthcare professionals need to instill the process of prevention, control and treatment of people infected with HIV into care practice. Through maintaining preventive treatment among HIV-infected pregnant women, it has been demonstrated that prophylactic antiretroviral therapy, scheduled cesarean section and the prohibition of breastfeeding significantly reduce vertical HIV transmission. This study aimed to assess the rates of vertical HIV transmission in a specialized service and iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 12 publications
1
10
0
Order By: Relevance
“…The small number of cases resulted in an inaccurate estimate, varying from 0.3%-13.8%, and prevented the estimation of the MTCT by region in the country. However, these values are compatible with regional variation reported in local studies: rates of 2%-3% in studies conducted in the South [ 16 , 17 ], Southeast [ 7 , 8 , 18 20 ] and Midwest [ 21 , 22 ], and rates close to 10% in the North [ 10 ] and Northeast [ 9 ] regions of the country. The detection rate of cases of AIDS in children under 5 years old in the country follows this same pattern, with the Southeast, South and Midwest regions showing the biggest reduction trends; 73.2%.…”
Section: Discussionsupporting
confidence: 88%
“…The small number of cases resulted in an inaccurate estimate, varying from 0.3%-13.8%, and prevented the estimation of the MTCT by region in the country. However, these values are compatible with regional variation reported in local studies: rates of 2%-3% in studies conducted in the South [ 16 , 17 ], Southeast [ 7 , 8 , 18 20 ] and Midwest [ 21 , 22 ], and rates close to 10% in the North [ 10 ] and Northeast [ 9 ] regions of the country. The detection rate of cases of AIDS in children under 5 years old in the country follows this same pattern, with the Southeast, South and Midwest regions showing the biggest reduction trends; 73.2%.…”
Section: Discussionsupporting
confidence: 88%
“…21 The percentage of mothers of infected children who received no prenatal care was similar in the present study, and a lack of prenatal care was considered a risk factor for increased MTCT. Other studies have also found an association between increased MTCT and no prenatal care 16,[22][23][24][25] The importance of administering ART during pregnancy has been known for some decades, and currently, with combined therapy, HIV MTCT rates have become significantly lower. 26 This was also confirmed in the current study which detected that no use or inappropriate ART use was related to higher MTCT rates.…”
Section: Discussionmentioning
confidence: 99%
“…Research across various regions of Brazil has shown that lack of antenatal care and late diagnosis underlie substantial gaps in the PMTCT cascade [ 8 , 12 , 18 20 ]. In our cohort, while 19% of case and 29% of control mothers were not diagnosed prior to birth because they had not attended any or abandoned antenatal care, 25% of case and 14% of control mothers did not receive their diagnosis due to a failure in antenatal services—tests not being available, not ordered, or results not reported.…”
Section: Discussionmentioning
confidence: 99%